Impact of Foreign Direct Investment on the Indian Economy - Tamizharasan, M (Journal of Commerce and Trade, 2018)
Foreign Direct Investment is an important instrument of economic development for developing countries. It provides a great drive for growth, after liberalization policy has been changed significant role in Indian economy. India is interested in increasing the FDI Inflows to earn more foreign exchange. This study investigate existence link between Foreign Direct Investment, Exports, Imports and Gross Domestic Product in the Indian economy. The objective of the study is to analyze growth and share of FDI, Gross Domestic Product, Exports and Imports and the relationship between FDI and Gross Domestic Product, Exports and Imports during the period from 1991 to 2015. The data are collected from Handbook of Statistics on Indian Economy 2016. This study analyse the index numbers, annual growth rate, averages, percentages, compound growth rate, simple linear regression and semi-log linear regression have been used. Classification-JEL : F14, F23, F43, F47